Iluminación de la cancha de fútbol barrio divino niño infraestructura red eléctrica (2021)
The purpose of this work is to carry out the lighting design of the soccer field in the Divino Niño neighborhood in the city of Cúcuta Norte de Santander, applying the latest trends in public lighting for sports fields that are being developed in the country as it is LED-type technology, which demands that these designs be carried out by qualified personnel and the application of RETILAP, where the equipment used in the lighting system meets the minimum technical requirements and that the LED-type luminaires used in the project have certified photometrics.